1999
DOI: 10.1095/biolreprod61.6.1468
|View full text |Cite
|
Sign up to set email alerts
|

Luteal Regression in the Primate: Different Forms of Cell Death During Naturaland Gonadotropin-Releasing Hormone Antagonist or Prostaglandin Analogue-Induced Luteolysis

Abstract: Morphological changes in the corpus luteum following natural and induced luteolysis in the marmoset were investigated by light and electron microscopy. Functional corpora lutea were studied in the mid and late luteal phase, naturally regressed corpora lutea in the early and late follicular phase, and corpora lutea induced to regress by administration of GnRH antagonist or prostaglandin F(2alpha) analogue in the midluteal phase. Natural luteolysis was associated with lutein cell atrophy, condensation of cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 37 publications
5
31
1
Order By: Relevance
“…This contrasts with observations on the characteristic effects of withdrawal of the trophic factor, luteinising hormone (LH), which have been described recently (Fraser et al 1999b, suggesting that anti-VEGF treatment does not markedly interfere with pituitary LH secretion.…”
Section: Discussioncontrasting
confidence: 68%
“…This contrasts with observations on the characteristic effects of withdrawal of the trophic factor, luteinising hormone (LH), which have been described recently (Fraser et al 1999b, suggesting that anti-VEGF treatment does not markedly interfere with pituitary LH secretion.…”
Section: Discussioncontrasting
confidence: 68%
“…Signifi cantly increased occurrence of lipids in cows with BCS1 and BCS2 was found also in our study, which indicates on the involvement of regressive mechanisms. Similar results were obtained also by Fraser et al [15], who found that natural luteolysis in primates was associated with lutein cell atrophy, condensation of cytoplasmic inclusions and organelles and increase in relative volume of lipids.…”
Section: Discussionsupporting
confidence: 90%
“…Progression through the ovarian cycle was determined by monitoring blood progesterone levels and ovaries were obtained during the follicular phase (early, n=3; mid, n=2; late, n=3) and were the same samples as those described by Fraser et al (1999), or during the luteal phase of the non-pregnant cycle and on day 21 of pregnancy. Tissues were fixed by immersion in 4% paraformaldehyde for 24 h and stored in 70% ethanol until processed into paraffin wax as described previously (Millar et al 1993).…”
Section: Tissue Collectionmentioning
confidence: 99%